2001
DOI: 10.1191/096032701718890603
|View full text |Cite
|
Sign up to set email alerts
|

Carbendazim-induced haematological, biochemical and histopathological changes to the liver and kidney of male rats

Abstract: Carbendazim is a systemic broad-spectrum fungicide controlling a wide range of pathogens. It is also used as a preservative in paint, textile, papermaking and leather industry, as well as a preservative of fruits. In the present study, carbendazim was administered at 0, 150, 300 and 600 mg/kg per day doses orally to male rats (Rattus rattus) for 15 weeks. At the end of the experiment, blood samples, liver and kidney tissues of each animal were taken. Serum enzyme activities, and haematological and bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
63
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 7 publications
(5 reference statements)
5
63
0
1
Order By: Relevance
“…The findings implies that the injection of pirimiphos-methyl is toxic to target and non-target organisms. These findings are in agreement with the work of Selmanoglu and Akay [36] who reported similar histopathological changes including mononuclear cell infiltration, congestion, hydropic degeneration and hepatocellular damage in the liver of male rats treated with dimethoate, endosulfan and carbaryl.…”
Section: Discussionsupporting
confidence: 93%
“…The findings implies that the injection of pirimiphos-methyl is toxic to target and non-target organisms. These findings are in agreement with the work of Selmanoglu and Akay [36] who reported similar histopathological changes including mononuclear cell infiltration, congestion, hydropic degeneration and hepatocellular damage in the liver of male rats treated with dimethoate, endosulfan and carbaryl.…”
Section: Discussionsupporting
confidence: 93%
“…On direct marrow examination, the great majority of mitoses (74% to 90%) were of erythroid lineage; only a few (0% to 10%) were granulocytic [18]. The alteration in number of RBC count and HGB content may be due to defective haematopoiesis, inhibited erythropoiesis or an increase in destruction of red blood cells [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Carbendazim exposure experimentally or occupationally, led to a decrease in the microsomal oxidation potential (Lisovska et al, 2005). Liver hypertrophy, hepatic necrosis, anomalous mitosis, induction of neoplastic nodules were some of the observations noted in experimental rats (Selmanoglu et al, 2001). However, Gray et al, reported that 400 mg/kg carbendazim did not cause any histopathological damage the liver of rats dosed from weaning until 105 days of age (Gray et al,1990).…”
Section: Figmentioning
confidence: 99%
“…Carbendazim (methyl-2-benzimidazole carbamate) is one of the broad spectrum fungicide currently widely used and it's major metabolite benomyl [methyl 1-(butylcarbamoyl)-2-benzimidazole carbamate] is also used as a fungicide (Vettorazzi, 1976). This compound is used as a preservative in paint, textile, paper and leather industry as well as a preservative of fruits (Selmanoglu et al, 2001). Carbendazim is an inhibitor of microtubule synthesis and directly alters testicular function through germ cell depletion and altering Sertoli and Leydig cell functions (Gray et al, 1989).…”
Section: Introductionmentioning
confidence: 99%